Polícia Militar do Espírito Santo: uma abordagem histórica, social e psicológica, sobre a formação e a violência - Ferro, Pedro Luiz (2018)
Frequently we hear a lot about the theme of public security and these are topics of wide discussion in the Social Sciences. The aim of this study was to draw a profile of the military police of the Espírito Santo state, through the analysis of the historical, social and political aspects. These aspects are aligned with the constituent elements of the work, with military and police activities with the production of identity. We analyzed the social identity of the military police as the conscience that the individual has to belong to a particular social and professional group. We also identified if the training received by de military police was effective. The data were obtained from questionnaires which were administered to100 military police from a formal training program of the Police Academy. This study took place at the Academy of Military Police of Espírito Santo (Cariacica-ES) and the 1st Battalion of Metropolitan Police (Vitória-ES). The interviews were divided into two stages: the first one between 2013 and 2015, and the second between 2015 and 2017. The questionnaires concentrated upon the police perceptions and responses toward different features of their courses and work. The interviews were transcribed and tabbed for the quantitative analysis of the answers. For the analysis of discourse, in order to identify rites and professional choice socialization processes were used as methodology the social representations of Moscovici (2010) and the social construction of reality of Berger and Luckmann (2012). As a result, about the professional choice, many declared that financial stability was the main factor, but there are cases where ideology and vocation are also important. More than half of respondents said that the image of the military police in the community is negative on the other hand, more than 90% responded that there is a good relationship with the community. Many consider important the subjects of “Human Rights” and “Socio Psychological Approach to Crime and Violence”. However, after a year of professional practice most of them said that they don't practice what they have learned in theory in the course of formation. That is there is a difference between theory and practice. We conclude that the social representations, i.e. the influence of veteran cops on then newest determine the behavior on the streets and violent actions. We also conclude that the training is not able to influence the conduct of most of the military officers who attend the Academy. Therefore, there is need for a continuous study to understand the reality of the military police and how they act in their field of action